An Unusual Cause of Spontaneous Pneumomediastinum: The Mounier-Kuhn Syndrome - Salim Naciri; Rachida Zahraoui; Mouna Soualhi; Jamal-Eddine Bourkadi (Case Reports in Pulmonology)
Mounier-Kuhn syndrome is a rare clinical and radiologic condition. It is characterized by tracheal and bronchial dilation. Diagnosis is made by computed tomography and bronchoscopy. An 81-year-old man presenting with an acute chest pain was referred to the pulmonology department. His chest computed tomographic scan showed a tracheobronchomegaly with an increase in the diameter of both the trachea and right and left main bronchi, associated with pneumomediastinum and fibrosis. Fiberoptic bronchoscopy revealed enlarged trachea and both main bronchi. These findings are consistent with a diagnosis of Mounier-Kuhn syndrome. Besides considering this long-neglected “orphan disease” when diagnosing spontaneous pneumomediastinum, clinicians should also be aware of an underlying Mounier-Kuhn syndrome in patients with recurrent respiratory infections, in order to avoid complications associated with the disease.